Modelling of macrophage responses to biomaterials in vitro: state-of-the-art and the need for the improvement - Piatnitskaia, Svetlana; Rafikova, Guzel; Bilyalov, Azat; Chugunov, Svyatoslav; Akhatov, Iskander; Pavlov, Valentin; Kzhyshkowska, Julia (Frontiers in Immunology, 2024)
The increasing use of medical implants in various areas of medicine, particularly in orthopedic surgery, oncology, cardiology and dentistry, displayed the limitations in long-term integration of available biomaterials. The effective functioning and successful integration of implants requires not only technical excellence of materials but also consideration of the dynamics of biomaterial interaction with the immune system throughout the entire duration of implant use. The acute as well as long-term decisions about the efficiency of implant integration are done by local resident tissue macrophages and monocyte-derived macrophages that start to be recruited during tissue damage, when implant is installed, and are continuously recruited during the healing phase. Our review summarized the knowledge about the currently used macrophages-based in vitro cells system that include murine and human cells lines and primary ex vivo differentiated macrophages. We provided the information about most frequently examined biomarkers for acute inflammation, chronic inflammation, foreign body response and fibrosis, indicating the benefits and limitations of the model systems. Particular attention is given to the scavenging function of macrophages that controls dynamic composition of peri-implant microenvironment and ensures timely clearance of microorganisms, cytokines, metabolites, extracellular matrix components, dying cells as well as implant debris. We outline the perspective for the application of 3D systems for modelling implant interaction with the immune system in human tissue-specific microenvironment avoiding animal experimentation.